Answered

Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

g(n)=n+3
f(n)=-n-5
Find g(3)-f(3)


Sagot :

Answer:

14

Step-by-step explanation:

g(3)=(3)+3

g(3)=6

f(3)=-(3)-5

f(3)=-8

6-(-8)=14

g(3)=(3)+3 - (f(3)=-(3)-5)

Simplify the functions, and use the distributive property.

g(3)=6 - f(3)=3+5

Continue to simplify:

g(3)=6 - f(3)=8

g(3)-f(3)=6-8

g(3)-f(3)=-2